Viral hepatitis - D. Brink (South African Family Practice)
The hepatitis A, B, C, D and E viruses primarily target the liver to cause viral hepatitis. Hepatitis A (HAV) and E (HEV) viruses are transmitted by the faecal-oral route and cause acute viral hepatitis. Acute viral hepatitis may be asymptomatic, with a rise in aminotransferase levels, it may be symptomatic, with or without jaundice, or it may present as fulminant hepatitis. The hepatitis B (HBV), C (HCV) and D viruses are parenterally transmitted and can cause acute and chronic infections. When they persist in the chronic carrier state they may cause chronic hepatitis, cirrhosis and hepatocellular carcinoma. The diagnosis of viral hepatitis in based on serology and molecular detection of the virus. There are no specific drug therapies available for patients with acute hepatitis A or hepatitis E infection, and management in based on symptomatic relief. Currently available treatments for chronic hepatitis B an C have limited efficacy, are expensive and may have severe side effects. Patients should be carefully selected and managed by a specialist with experience in this field. Vaccines are available for HAV and HBV.